A study of hepatitis C prevalence in healthcare workers in the West of Scotland. Issue 1 (1st January 2001) - Thorburn, D; Dundas, D; McCruden, E A B; Cameron, S O; Goldberg, D J; Symington, I S; Kirk, A; Mills, P R
Abstract : BACKGROUND AND AIMS: Whether healthcare workers have an increased prevalence of hepatitis C virus infection as a result of exposure to patient's blood and body fluids is controversial. This study assesses the prevalence of hepatitis C virus infection in healthcare workers, and its relation to the performance of exposure prone procedures and duration of occupational exposure, allowing an estimate to be made of the incidence of occupationally acquired hepatitis C infection among medical staff. METHODS: In this anonymous retrospective cohort study, we estimated the prevalence of hepatitis C infection in 10 654 healthcare workers. ELISA-3 testing was performed on pools of five sera collected during immunisation against hepatitis B. Healthcare workers were arranged into five occupational groups, according to the degree of patient exposure, and three age bands (<30 years, 30–39 years, >40 years). RESULTS: Prevalence of antibodies to hepatitis C was 0.28% (30/10 654), comparable in all occupational groups (p=0.34) and unrelated to duration of potential exposure. Assuming that all detected infections had been occupationally acquired, the maximum estimated risk of hepatitis C infection in exposure prone medical staff was low: 1.4% for surgeons and 1.0% for physicians over a 35 year professional career. CONCLUSIONS: Hepatitis C infection is infrequent in healthcare workers in Glasgow. Those conducting exposure prone procedures do not seem to be at higher risk than other healthcare staff.